Describing the Undescribed (The Odd Revenue Sharing of PSAK No. 59) - Hendi Yogi Prabowo (Jurnal Akuntansi dan Auditing Indonesia, 2004)
The establishment of Indonesian Islamic Banking Accounting Standard in 2002 has indeed solved some accounting – related problems, nevertheless, many others are raising along with the socialization of such a standard. The major current accounting problems are usually related to the lack of understanding toward the “never seen before” theory of accounting. This article discusses one of the most controversial issues related to PSAK (Pernyataan Standar Akuntansi Keuangan/Statements of Financial Accounting Standards) No. 59 named “revenue sharing”. The main purpose of this article is to reveal what was once unrevealed in PSAK No. 59’s paragraphs of revenue sharing standard. This purpose is important in nature considering the reality that PSAK No. 59 is much too general to be directly implemented in real banking practice. This article analyzes revenue sharing by referring to some previously recognized theories of accounting including AAOIFI’s. The other and most important mean to analyze the hidden meaning of PSAK No. 59’s paragraphs in this article is PAPSI (Pedoman Akuntansi Perbankan Syariah Indonesia), the technical interpretation of PSAK No. 59. As the analysis goes through two directions; business and accounting, this article is strengthening the thought that accounting is never an exact science, because it is by nature that accounting is socially constructed. Keywords: Islamic Bank, PSAK No. 59, AAOIFI, PAPSI, return sharing, revenue sharing, profit sharing